Multidisciplinary management of skeletal class III malocclusion with unilateral condylar hyperplasia and missing mandibular first molar: a case report - Wenzhen Gao; Lanxin Zhang; Yongyao Wu; Yiting Ze; Chenchen Zhou; Qing Zhao (BMC Oral Health)
Abstract Condylar hyperplasia (CH) is a developmental disorder characterized by excessive and progressive condyle growth, leading to facial asymmetry, malocclusion, and temporomandibular joint dysfunction. The timing and selection of treatment approaches are crucial for optimal outcomes. In this case, we implemented a four-year conservative management strategy, comprising two years of passive observation followed by two years of pre-surgical orthodontics, enabling conservative treatment while avoiding the potential risks. The long-term absence of the mandibular first molar resulted in alveolar ridge atrophy, presenting challenges for orthodontic or implant treatments. Through the integration of periodontally accelerated osteogenic orthodontics (PAOO), we achieved significant posterior tooth mesial movement (5 mm) within three months in the atrophic region, establishing stable and functional occlusal relationships.